Trade-Union Activism Among University Teachers During Cameroon’s Political Liberalisation (Nordic Journal of African Studies, 2004)
Academic staff trade unions in universities have succeeded in preserving a considerable degree of autonomy versus the state in a number of West African countries since independence, enabling them to play a significant role in the defence of their members’ interests. Cameroon forms an exception in the region as it was not until political liberalisation in the early 1990s that an autonomous academic staff trade union emerged there. This article examines the role of this trade union amidst the deep crisis bedevilling the university system in Cameroon. Faced with apparent government insensitivity to its demands, it has displayed a considerable degree of militancy but its failure to achieve important gains for its members has, it will be argued, been mainly due to the government’s evasive and repressive strategies. Only recently have the government and the university authorities become more prepared to solve university teachers’ contractual problems and grievances through dialogue and negotiation.